A Differential Approach to Undefined Behavior Detection. - Xi Wang; Zeldovich, Nickolai; Kaashoek, M. Frans; Solar-Lezama, Armando (Communications of the ACM, 2016)
This paper studies undefined behavior arising in systems programming languages such as C/C++. Undefined behavior bugs lead to unpredictable and subtle systems behavior, and their effects can be further amplified by compiler optimizations. Undefined behavior bugs are present in many systems, including the Linux kernel and the Postgres database. The consequences range from incorrect functionality to missing security checks. This paper proposes a formal and practical approach, which finds undefined behavior bugs by finding “unstable code” in terms of optimizations that leverage undefined behavior. Using this approach, we introduce a new static checker called Stack that precisely identifies undefined behavior bugs. Applying Stack to widely used systems has uncovered 161 new bugs that have been confirmed and fixed by developers.